Políticas linguísticas e políticas educacionais: prefiguração e performatização de identidades em Moçambique - Macaringue, Ilidio Enoque Alfredo (2020)
Mozambique, the locus of the research, as a modern nation-state, resulted from the armed struggle for national liberation unleashed by FRELIMO (Mozambique Liberation Front), from 1964 to 1974, which overthrew the Portuguese colonial system and guaranteed the proclamation of national independence in 1975. For the construction and consolidation of the nation-state, Portuguese was chosen as the official language and language of national unity (MACHEL, 1978), in a sociolinguistic context dominated by the Bantu languages. Indeed, in this thesis I have as general objective to understand how the identity processes are prefigured and/or performed in linguistic and educational policies in Mozambique. The research is enrolled in the area of Transgressive Applied Linguistics (PENNYCOOK, 2006), undisciplinary, Interdisciplinary and Transdisciplinary (MOITA LOPES, 2006), and was developed based on the post-colonial approach (SOUSA SANTOS, 1998; 2003; MOITA LOPES, 2006; MIGNOLO, 2010; MAKONI; MEINHOF, 2006; QUIJANO, 2010) and post-structuralist (PENNYCOOK, 2006), from the socio-historical and cultural perspective. Based on the analysis and interpretation of data that includes various laws, historical documents, linguistic landscapes and excerpts from news and opinion articles published in newspapers, I found that language policies and educational policies in Mozambique, as instruments of territory management and ethnic-linguistic and cultural plurality, they are strictly associated with the pre-figuration of national identity. As a result, both do not fully reflect the challenges and concerns of a significant part of society, as violations of linguistic and human rights still persist, especially when citizens do not have equal access to public services such as ministries, courts, police stations, as well as consumer goods, information and full school education in their respective native languages, because the language that unites, inversely separates and exclude, by creating selective barriers to the effective integration of citizens into society. Furthermore, I defend the need to adjust, as a national collectivity, the conceptions about language studies in globalized societies, such as the Mozambican one, in order to problematize and denaturalize the idea of the existence of pure and uniform languages, in other words, pre-given (PENNYCOOK, 2006), as you let yourself believe with the Portuguese standard norm,that is a socio-cultural construct (an hypostasis), according to Bagno (2011), imposed by the national identity pre-figuration policies (PINTO, 2013). With that, other rationalities of language practices that reflect the multiple and the super-diverse could be seen, in which identities are performed in discourse and in bodily actions (MOITA LOPES, 2013a; BUTLER, 2003; PENNYCOOK, 2006; PINTO, 2007), as well as in the translational practices that are legitimized by the socio-historical, cultural and ideological contexts of the respective socially situated and ideologically marked subjects, to see what was not seen (PIRES-SANTOS et al., 2015), hear yourself listening to other (MENEZES DE SOUZA, 2011), and have a plural linguistic stance (ALTENHOFEN; BROCH, 2011) that allows to guarantee the voice and to listen (ALTENHOFEN, 2013), beside of integrating different differences (CAVALCANTI; MAHER, 2009) on the teaching practice of the language teacher, with recourse to the pedagogy of languages (GARCÍA, 2009; CANAGARAJAH, 2013; CAVALCANTI, 2013; YIP; GARCÍA, 2018; GARCÍA; LEIVA, 2014) and the culturally relevant pedagogy (LADSON-BILLINGS, 2002).